(untitled) (Journal of Dhaka Medical College, 2015)
Polydactyly or hyperdactyly is a congenital physical anomaly and is a common congenital digital variation affecting the hand and foot. It may present as a range of defects from minor soft tissue duplications to major bony abnormalities. Of the different varieties the post-axial one is the commonest. Polydactyly may appear as isolated or in association with other birth defects. For proper management a comprehensive knowledge of this condition is required for medical experts particularly the pediatric orthopedic surgeons. Here we report a case of hexadactyly (six fingers) in all four limbs of a neonate. This neonate was free from other congenital anomaly. Photograph and radiographs revealed the anatomical abnormalities, which is essential for proper planning of the future management. DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21547 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 219-222